NANOCRYSTALS AS MODEL SYSTEMS FOR PRESSURE-INDUCED STRUCTURAL PHASE TRANSITIONS - Jacobs K.; Alivisatos A.P. (My University, 2001)
An understanding of first-order pressure-induced structural transitions is relevant to many research areas in geological and planetary sciences because it involves the study of materials exposed to high pressures. For example, solid-solid transitions in silicates are responsible for the seismic discontinuities in the earth’s mantle (Chudinovskikh and Boehler 2001) and may play a role in plate tectonics and deep earthquakes (Kirby et al. 1991). In geological applications, models of structural transition kinetics simulate rock formation taking place over millions of years (Shekar and Rajan 2001). Despite their importance in earth science applications, the microscopic processes of solid-solid phase transitions are difficult to study in the bulk solid for several reasons (Putnis 1992). In extended solids, the transformation nucleates at defects, which are present at equilibrium even in the highest quality crystals. As a transformed region of the crystal grows larger, mechanical forces generate new defects, which in turn act as new nucleation sites. The difficulties in bulk are compounded by the irreversibility of the kinetics, which depends strongly on the preparation of the sample and its history. The study of first-order phase transitions can be greatly simplified in nanocrystal systems because small crystals can behave as single structural domains and reproducibly cycle through multiple transitions (Wickham et al. 2000). To illustrate the advantages of the simple kinetics in nanoscale systems in exploring fundamental questions of structural phase transitions, this chapter focuses on the CdSe nanocrystal system. Nanocrystalline solid-solid transitions in geologically relevant material such as Fe2O3 nanocrystals are also now being studied (Rockenberger et al. 1999), and a comparable understanding of these materials is a current research goal. The CdSe nanocrystals are a particularly well-controlled and characterized test system (Tolbert et al. 1995). The nanocrystals consist of hundreds to thousands of covalently bonded atoms, synthesized as nearly …